Theory of non-steady state electrical characteristics of metal-insulator-metal structures with schottky barriers and exponentially distributed impurity states - Gupta, H. M. [UNESP] (Wiley, 1996)
We discuss non-steady state electrical characteristics of a metal-insulator-metal structure. We consider an exponential distribution (in energy) of impurity states in addition to impurity states at a single energy level within the depletion region. We discuss thermal as well as isothermal characteristics and present an expression for the temperature of maximum current (Tm) and a method to calculate the density of exponentially distributed impurity states. We plot the theoretical curves for various sets of parameters and the variation of Tm, and Im (maximum current) with applied potential for various impurity distributions. The present model can explain the available experimental results. Finally we compare the non-steady state characteristics in three cases: (i) impurity states only at a single energy level, (ii) uniform energetic distribution of impurity states, and (iii) exponential energetic distribution of impurity states.
Keywords: Composite structures; Crystal defects; Electronic density of states; Electronic structure; Theory; Metal-insulator-metal structures; Schottky barriers; Electric conductivity of solids